5G and Blockchain Enabled Lightweight Solutions for Containing COVID-19. (15th February 2022) - Kamal, Mohsin; Aljohani, Abdulah Jeza; Alanazi, Eisa; Albogamy, Fahad R.
Abstract : Due to the global pandemic of COVID-19, there is an urgent need to utilize existing technologies to their full potential. Internet of things (IoT) is regarded as one of the most trending technologies with a great potential in fighting against the coronavirus outbreak. In this study, we examine the current status of IoT applications related to COVID-19, identify their deployment and operational challenges, and suggest possible opportunities to further contain the pandemic. Furthermore, we perform analysis by examining the IoT implementation in which internal and external factors are discussed. We suggest by presenting results that lightweight security algorithms, blockchain-based solutions for enabling end-to-end security and privacy, and 5G for IoT devices to tackle the bandwidth issues for scalable IoT networks are few of the solutions in containing the COVID-19.